NOTO: MENGUAK YANG TERBUNGKAM - joko aswoyo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
The show entitled Noto represents an elaboration of dance, music, literature, visual art, and light. This show collaborate artistic expressions among artists from various fields starting from their respective experiences and artistic backgrounds. The results of this exploration and collaboration were presented on the prosenium stage. The show’s collaboration aims to find the meeting point between NotoSoeroto and Piet Mondrian through the theosophy and spiritualism. The search process also translates the similar symptoms between the two, both the background of the beliefs, the artistic expressions that each uses. The search results were then dialogue, using their artistic languages, in the work of art exploration and collaboration to produce the show entitled Noto.